Inclusive Journalism on Disability News in TribunSumsel.com during Covid 19 Pandemic Era - Andarini, Rindang Senja (MediaTor (Jurnal Komunikasi), 2022)
Reports in the mass and online media tend to present people with disabilities in an insufficient representation. When people with disabilities are portrayed in the news, they are often marked by the stigma attached by society. This shows the importance of directing the approach of journalists toward inclusive journalism. This research aims to examine how the representation of different abilities is portrayed in the local online media TribunSumsel.com. This research uses the framing analysis method of Zhongdang Pan and Gerald M. Kosicki. The results of the research show that many news of TribunSumsel.com presented a positive portrayal of people with different ability by avoiding the use of stereotypical language or phrases. However, in terms of news sources, this media more often used non-disabled sources, even in disability news. In other topics, people with disabilities were not involved as news sources. The use of images was still focused on people with physical disabilities, while other disabilities were not raised. In addition, the portrayal of people with different abilities as inspiring objects still stood out (inspiration porn). This result showed that the media still needs to apply the principles of inclusive journalism.